Hyper IgE Syndromes: Understanding, Management, and Future Perspectives: A Narrative Review - Mohammad Salehi; Zeinab Neshati; Hamid Ahanchian; Rana Tafrishi; Alireza Pasdar; Mojtaba Safi; Ehsan Ghayoor Karimiani (Health Science Reports)
ABSTRACT Background and Aim Hyper IgE syndromes (HIES) are rare primary immunodeficiency characterized by susceptibility to specific infections, eczema, and elevated IgE levels. Pathogenic mutations in STAT3, IL6R, IL6ST, ERBB2IP, PGM3, ZNF431, SPINK5, TGFBR1/2, and CARD11 have been identified as genetic factors contributing to phenotypes of HIES lead to hindered differentiation and activity, aberrant signaling cascades and disrupting immune regulation. HIES present a diverse clinical symptoms, challenging diagnosis and management; understanding its pathophysiology, genetics, and immunological abnormalities offer hope for improved outcomes. In this review we aim to provide a comprehensive understanding of the condition and also discuss latest updates on pathological features, clinical spectrum and its variability, immunological abnormalities, inheritance patterns, new candidate genes, challenges, management strategies, epidemiology and future directions of HIES. Methods This review conducted an extensive search of information from multiple databases, including PubMed, Scopus, WHO, and ClinVar to ensure comprehensive coverage. Preference was given to articles published recently to capture the latest research and developments. Endnote was employed as a reference manager. The relevant literature was meticulously reviewed to address the objectives of the study. Results Missense, nonsense, and frameshift variants are commonly observed in HIES. Understanding these genetic mutations is key to diagnosing and managing conditions such as Hyper‐IgE recurrent infection syndromes (linked to IL6R, STAT3, and ZNF341 mutations), Atopy associated with ERBIN mutations which links STAT3 and TGF‐β pathway, Immunodeficiency 23 (caused by PGM3 mutations), Netherton syndrome (resulting from SPINK5 mutations), and Loeys‐Dietz syndrome (related to TGFBR mutations). Each year, new genes and variants responsible for this type of immune deficiency are added to the list. Conclusion Although rare, HIES significantly impacts patients due to its complex medical manifestations and need for lifelong management. Identifying casual variants is essential for effective clinical management of these complex conditions.